نضرة فرحات عباس لمفهوم الاستقلال والدولة من خلال كتاباته - دزيريه بله باسي; سارة حنيش (جامعة الوادي - University of Eloued, 2025)
سعينا من خلال دراستنا لمفهوم الاستقلال والدولة في فكر فرحات عباس ، الذي يعتبر من الشخصيات البارزة في الخركة الوطنية والثورة التحريرية الجزائرية عام 1954، إلى استكشاف أيديولوجيته استنادا إلى كتاباته والأفكار التي تبناها، كما نهدف إلى رسم صورة واضحة المعالم لرؤيته حول تحقيق مشروع الدولة الحزائرية المستقلة، مستندين إلى الأسس التي أقرتها الثورة التحريرية من خلال بيان أول نوفمبر. بالإضافة إلى ذلك، حاولنا في هذه الدراسة تتبع التحولات التي شهدتها شخصيته والوقوف عند أبرز المحطات في تاريخه النضالي الغني بالمواقف والأحداث ، من بينها مشاركته في الثورة التحريرية المباركة بعد فشل سياسة الإدماج واقتناعه بالعمل المسلح ومعارضته للنظام الاشتراكي ودستور 1963 الذي وضعه "بن بله" بعد الاستقلال مما جعله يلقب برجل التحولات. "Summary In our study, we aimed to explore the concept of independence and the state in the thought of Farhat Abbas, a prominent figure in the national movement and the Algerian liberation revolution of 1954. We sought to examine his ideology based on his writings and the ideas he embraced. Our goal was to provide a clear picture of his vision for achieving the project of an independent Algerian state, grounded in the principles established by the liberation revolution through the November 1st Declaration. Additionally, we attempted to trace the transformations in his character and highlight key milestones in his rich history of activism, including his participation in the blessed liberation revolution following the failure of the integration policy, his conviction in armed struggle, and his opposition to the socialist system and the 1963 constitution established by Ben Bella after independence, which earned him the title of the man of transformations. Keywords: Farhat Abbas, independence, foundations of the state."
مذكرة ماستر قسم علوم انسانية تخصص تاريخ المغرب العربي المعاصر
Keywords: أسس الدولة; الاستقلال; فرحات عباس; Farhat Abbas; independence; foundations of the state.